Baseball genius - Green, Tim, 1963-; Jeter, Derek, 1974- (Green, Tim, 1963- Baseball genius., 2018)
Jalen DeLuca's dad doesn't have the money to keep him on his traveling baseball team, so Jalen decides he'll find a way to cover the fees himself. But when he sneaks into the home of New York Yankee's second baseman, James Yager, and steals a couple of balls that he hopes to sell for cash, he's caught by Yager. Desperate to get out of trouble, Jalen shares a secret--he has a strange ability to predict baseball pitches. Yager agrees not to press charges if Jalen helps him out of his batting slump, a slump that could get him replaced by a younger player.